Family Persuasive Communication Against Covid-19 Prevention Attitudes in Pajang Village, Tangerang City - Fadmawaty, Ani; Sari, Dewi Indah; Wasludin, Wasludin; Mustika, Suci Meliana (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Background: Persuasive communication is one method of communication that can influence or change the attitude of others. Persuasive communication is very important in the family, because the role of the family is very influential in shaping the character of children. A persuasive communication approach, the head of the family can provide direction, guidance and examples to children such as providing a better understanding of the prevention of Covid-19 by family members so that they can improve a good attitude in preventing Covid-19. Purpose : find out the relationship of family persuasive communication to the attitude of preventing Covid-19 in the community in RT 001/003 Pajang Village, Tangerang City Methods : This type of research is quantitative research with cross sectional design. The sample is 211 people. The sampling technique is purposive sampling. Results : There is a significant relationship between family persuasive communication on the attitude of preventing Covid-19 in the community in RT 001/003 Pajang Village, Tangerang City with p value: 0.026. Conclusion : show that most respondents use family persuasive communication, namely persuasive as many as 117 respondents (55.5%) and positive Covid-19 prevention attitudes as many as 120 respondents (56.9%). Based on a bivariate analysis between family persuasive communication on Covid-19 prevention attitudes (p value: 0.026), which means that there is a significant relationship between family persuasive communication and Covid-19 prevention attitudes in the community in RT 001/003 Pajang Village, Tangerang City.